2005
DOI: 10.1109/tbme.2005.847555
|View full text |Cite
|
Sign up to set email alerts
|

Error Grid Analysis of Noninvasive Glucose Monitoring Via Gingival Crevicular Fluid

Abstract: In order to realize a noninvasive blood glucose monitor, we monitored the gingival crevicular fluid (GCF). In this paper, the clinical evaluations were performed on not only normal subjects but also diabetic subjects using a GCF-glucose monitor to determine blood glucose levels. Meal load tests were carried out and the time-course changes in blood glucose level and GCF glucose level were measured continuously. A positive correlation of more than 0.9 was found between blood glucose level and GCF glucose level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Research has explored the dental office as a strategic venue of opportunity for glucose testing, examining the possibility of using gingival crevicular fluid (GCF) for diabetes screening 8–10 . Measuring glucose in GCF is a promising approach, yielding moderate to good correlations with capillary blood glucose measures 8–10 . However, the need for special equipment and the length of time necessary to collect a sufficient sample for analysis suggest that such an approach would have limited use and appeal in busy dental practices.…”
mentioning
confidence: 99%
“…Research has explored the dental office as a strategic venue of opportunity for glucose testing, examining the possibility of using gingival crevicular fluid (GCF) for diabetes screening 8–10 . Measuring glucose in GCF is a promising approach, yielding moderate to good correlations with capillary blood glucose measures 8–10 . However, the need for special equipment and the length of time necessary to collect a sufficient sample for analysis suggest that such an approach would have limited use and appeal in busy dental practices.…”
mentioning
confidence: 99%
“…showed that 77% of US dentists felt that it was important for dentists to conduct screening for type 2 diabetes, while only 56% felt comfortable testing blood via the finger‐stick method. Gingival crevicular fluid (GCF) 80 has also been used to assess glucose levels; however, its correlation with peripheral blood was not as high as that of GCB samples.…”
Section: Diabetes Screeningmentioning
confidence: 99%
“…Likewise the gingival tissues of these patients bleed during the gentle provocation of the tissues associated with a routine dental and periodontal examination. Several studies have shown that in diabetic subjects glucose levels in capillary blood obtained from “finger sticks” correlate with glucose levels from blood obtained from gingival sulci or periodontal pockets during routine periodontal examinations [104112]. Although early studies reported moderate to good correlations between the glucose levels in gingival crevice blood and capillary blood, the length of time required for collection of samples and the need for special equipment and supplies for sample collection and analysis made the use of gingival blood samples cumbersome and inconvenient [104106].…”
Section: Potential Diagnostic Components Of Gingival Crevicular Fluidmentioning
confidence: 99%
“…Several studies have shown that in diabetic subjects glucose levels in capillary blood obtained from “finger sticks” correlate with glucose levels from blood obtained from gingival sulci or periodontal pockets during routine periodontal examinations [104112]. Although early studies reported moderate to good correlations between the glucose levels in gingival crevice blood and capillary blood, the length of time required for collection of samples and the need for special equipment and supplies for sample collection and analysis made the use of gingival blood samples cumbersome and inconvenient [104106]. Parker et al 1993 [113] tested the use of commercially available reagent strips and an in-home glucose monitoring device for the purpose of measuring glucose levels in gingival crevicular blood and found that 92% of glucose levels from gingival crevice blood samples were within acceptable levels of measurement error compared to 90% from capillary blood samples.…”
Section: Potential Diagnostic Components Of Gingival Crevicular Fluidmentioning
confidence: 99%